2011
DOI: 10.1209/0295-5075/94/56001
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility windows and phase transitions of ordered and disordered ANA framework zeolites

Abstract: The analcime-like feldspathoids are a group of microporous minerals with the ANA framework topology. Analcime proper has predominantly Na as its channel cation content, while leucite contains predominantly K, pollucite contains Cs and wairakite contains Ca. Under compression, all these minerals display structural displacive phase transitions to low-symmetry forms at relatively low pressures (0.5-3.2 GPa). We show, using geometric simulation, that these phase transitions are controlled by the "flexibility windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Remarkably, our results are even sensitive to Al/Si ordering in the framework. Geometric simulations for wairakite, which displays Al/Si ordering, match the experimental data when ordering is included but not when a uniform average T-O distance is used [13].…”
Section: Ana Group Zeolitesmentioning
confidence: 84%
See 2 more Smart Citations
“…Remarkably, our results are even sensitive to Al/Si ordering in the framework. Geometric simulations for wairakite, which displays Al/Si ordering, match the experimental data when ordering is included but not when a uniform average T-O distance is used [13].…”
Section: Ana Group Zeolitesmentioning
confidence: 84%
“…Locations of the phase transitions of wairakite (W) and leucite (L) are indicated by arrows. Modified from [13] Fig. 2 P-V data for analcime (green triangles) and pollucite (red squares) annotated with results of geometric simulation.…”
Section: Silicalitementioning
confidence: 99%
See 1 more Smart Citation
“…Using geometric simulation we have shown that this transition occurs when the structure reaches the edge of its cubic flexibility window [41]. This insight extends to other minerals with the ANA framework—leucite, pollucite and wairakite [42]—and in wairakite, Al/Si ordering in the framework is significant [43]. …”
Section: Applications Of Geometric Analysis and Simulationmentioning
confidence: 89%
“…This idealization of the zeolite framework, as a periodic truss of rigid tetrahedra, has led to several insights into their structural properties. Zero-frequency RUMs have been discovered, and their role in phase transitions and the absorption properties of framework materials has been investigated [15,16,[29][30][31]. It has also been discovered that all of the known zeolite frameworks are flexible, exhibiting a range of densities over which volume changes are absorbed by tetrahedral rotations, without generating any stresses [19,21].…”
Section: Zeolites As Three-dimensional Periodic Trussesmentioning
confidence: 99%